Accounting students’ perceptions on skills and personal attributes needed for success in accounting career: a case of northern UiTM / Roshima Said ... [et al.] - Said, Roshima; Radjeman, Leily Adja; Abdul Rahman, Nor Hafizah; Ismail, Noridah (2007)
The purpose of this research is to investigate the perception of Universiti Teknologi MARA accounting students' towards the importance of skills and personal attributes needed towards their career accounting development. A random sample of 433 accounting students from three institutions of Universiti Teknologi MARA (UiTM) i.e. (UiTM) Kedah, UiTM Perlis and UiTM Perak were selected for the study.